Pakistan Intra-industry Trade: A Panel Data Approach - Shahbaz, Muhammad; Leitao, Nuno Carlos; Butt, Muhammad Sabihuddin (International Journal of Economics and Financial Issues, 2012)
This study examines the determinants of intra-industry trade (IIT) between Pakistan and trade patterns in the period 1980-2006, using a static and dynamic panel data approach. In the recent years, the government of Pakistan had realized factors to liberalize the international trade. The literature of international economics demonstrates that this condition (trade liberalization) induces the IIT. The case study for Pakistan has been negligence in the economic literature. This study uses country-specific characteristics as explanatory variables. This study utilizes country-specific characteristics as explanatory variables. The empirical evidence indicates that IIT is a negative function of the difference in GDP per capita between Pakistan and her trading partners. Furthermore, econometric results point out that trading is influenced by the similar demand. We have also introduced an economic dimension; this proxy confirms the positive effects of IIT. Our findings reveal the importance of scales economies and the variety of differentiated products. The study supports to accept the hypothesis that trading increases if the transportation costs decrease. Keywords: Intra-industry trade; Pakistan; Comparative advantage; Panel data JEL Classifications: C20; C30; F12